Effect of mineral admixtures on fresh, mechanical and durability properties of RAP inclusive concrete. (15th December 2017) - Singh, Surender; Ransinchung, G.D.; Kumar, Praveen
Highlights: Effect of silica fume, fly ash and bagasse ash in RAP concrete is studied. Significant improvement in mechanical properties of RAP concrete. Inclusions of mineral admixtures densified microstructure significantly. Equation to predict flexural from compressive strength was established. Abstract: This study deals with improvement in the properties of ABTRAP (Beneficiated RAP aggregates by Abrasion & Attrition technique) inclusive concrete by incorporating mineral admixtures such as Silica Fume (SF), Fly ash (FA) and Sugarcane Bagasse Ash (SCBA). 6 mixes were prepared by partially replacing Ordinary Portland Cement (OPC) by SF (5% &10%), FA (10% & 20%) and SCBA (5% & 10%). Maximum improvement in compressive, flexural and split tensile strength of ABTRAPC mix was found when 10% OPC was part replaced by SF followed by 20% replacement by FA and 5% replacement by SCBA. Even SF20 mix showed comparable strength to that of natural aggregate concrete (NAC) mix. Reductions in permeable voids, water absorption, initial rate and coefficient of water absorption and improved abrasion resistance was observed for all the considered mixes. A power regression equation (flexural strength = 0.368 × (compressive strength) 0.72 ) of high co-relation (R 2  = 0.93) was established to predict flexural strength from compressive strength results of ABTRAPC mixes. Based on the finding of the present part of investigation, it is recommended to replace 10% OPC by SF, FA (20% in sulphate free environment) and 5% by SCBA in ABTRAP inclusive concrete mixes.